Resenha: After The Revolution: Twenty Years of Portuguese Literature, 1974-1994. Editado por: Helena Kaufman e Anna Klobucka. Lewisburg: Bucknell University Press; London: Associated University Press, 1997. 252 p. (Revista do Centro de Estudos Portugueses, 1998)
.